Susceptible cell lines for the production of porcine reproductive and respiratory syndrome virus by stable transfection of sialoadhesin and CD163 - Delrue, Iris (BioMed Central, 2010)
BACKGROUND: Porcine reproductive and respiratory syndrome virus (PRRSV) causes major economic losses in the pig industry worldwide. In vivo, the virus infects a subpopulation of tissue macrophages. In vitro, PRRSV only replicates in primary pig macrophages and African green monkey kidney derived cells, such as Marc-145. The latter is currently used for vaccine production. However, since virus entry in Marc-145 cells is different compared to entry in primary macrophages, specific epitopes associated with virus entry could potentially alter upon growth on Marc-145 cells. To avoid this, we constructed CHO and PK15 cell lines recombinantly expressing the PRRSV receptors involved in virus entry into macrophages, sialoadhesin (Sn) and CD163 (CHO(Sn-CD163 )and PK15(Sn-CD163)) and evaluated their potential for production of PRRSV. RESULTS: Detailed analysis of PRRSV infection revealed that LV and VR-2332 virus particles could attach to and internalize into the CHO(Sn-CD163 )and PK15(Sn-CD163 )cells. Initially, this occurred less efficiently for macrophage grown virus than for Marc-145 grown virus. Upon internalization, disassembly of the virus particles was observed. The two cell lines could be infected with PRRSV strains LV and VR-2332. However, it was observed that Marc-145 grown virus infected the cells more efficiently than macrophage grown virus. If the cells were treated with neuraminidase to remove cis-acting sialic acids that hinder the interaction of the virus with Sn, the amount of infected cells with macrophage grown virus increased. Comparison of both cell lines showed that the PK15(Sn-CD163 )cell line gave in general better results than the CHO(Sn-CD163 )cell line. Only 2 out of 5 PRRSV strains replicated well in CHO(Sn-CD163 )cells. Furthermore, the virus titer of all 5 PRRSV strains produced after passaging in PK15(Sn-CD163 )cells was similar to the virus titer of those strains produced in Marc-145 cells. Analysis of the sequence of the structural proteins of original virus and virus grown for 5 passages on PK15(Sn-CD163 )cells showed either no amino acid (aa) changes (VR-2332 and 07V063), one aa (LV), two aa (08V194) or three aa (08V204) changes. None of these changes are situated in known neutralizing epitopes. CONCLUSIONS: A PRRSV susceptible cell line was constructed that can grow virus to similar levels compared to currently available cell lines. Mutations induced by growth on this cell lines were either absent or minimal and located outside known neutralizing epitopes. Together, the results show that this cell line can be used to produce vaccine virus and for PRRSV virus isolation.